Peran Akuntansi Forensik dan Audit Investigasi dalam Mengungkap Fraud dengan Whistleblowing sebagai Variabel Intervening: Studi Kasus Siklus Inventori di PT Vale Indonesia, Sulawesi Selatan - Muhammad Su'un; Muhammad Abduh (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to uncover fraud behavior in the supply cycle through forensic accounting and investigative auditing methods using whistleblowing as an intervening variable. The study uses a quantitative approach based on post-positivist philosophy with purposive sampling. Data were obtained from 45 respondents and analyzed using Partial Least Squares (PLS)-SEM with the help of SmartPLS 3.0 software. The results showed that forensic accounting has no significant effect on the disclosure of fraud in the inventory cycle. On the contrary, investigative audits have a positive and significant effect on the disclosure of fraud. In addition, investigative audits also have a positive and significant effect on whistleblowing, which implies that the stronger the investigative audits in an organization, the more likely it is that someone will report fraud. This study also found that whistleblowing does not mediate the effect of forensic accounting on fraud, but it does mediate the effect of investigative audits on fraud. The novelty of this study is that it analyzes the relationship between forensic accounting, investigative audits and whistleblowing on the supply cycle, which has been little studied empirically in academic literature. In addition, this study highlights the role of whistleblowing as a more effective reporting mechanism to support investigative audits, whereas forensic accounting does not. These findings indicate that companies need to further optimize investigative audits to detect fraud, as this approach has been proven to be more effective in encouraging whistleblowing and exposing fraud compared to forensic accounting. In addition, companies need to strengthen their whistleblower protection systems so that they feel safe in reporting fraud without fear of retaliation. The results of this study can be used as a basis for policymakers, auditors, and regulators to improve internal control systems to ensure compliance with Financial Accounting Standards (SAK) in Indonesia.